Effects of chronic heat stress on cellular immunity in Japanese quail (Coturnix coturnix) - Videla, E. A. (2017)
Fil: Videla, E. A. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones Biológicas y Tecnológicas; Argentina.